Diabetic Retinopathy in Type 2 Diabetes Mellitus Patients Attending the Diabetic Clinic of the University of Gondar Hospital, Northwest Ethiopia - Asamere Tsegaw; Shitaye Alemu; Abere Dessie; Christopher C. Patterson; Eldryd H. O. Parry; David I. W. Phillips; Elisabeth R. Trimble (Journal of Ophthalmology)
Objective. To investigate the level of diabetic retinopathy in type 2 diabetes (T2DM) patients attending the University of Gondar Hospital (UGH) Diabetic Clinic, Northwest Ethiopia. Methods. An audit was carried out involving a total of 739 T2DM patients attending at the diabetic clinic of UGH. They represented approximately 90% and 50% of all T2DM patients under regular review at the urban and rural diabetic clinics of UGH, respectively. All were supervised by the same clinical team for a long period. Eye examinations were performed for visual acuity, cataract, and retinal changes (retinal photography and slit-lamp biomicroscopy). Body mass index (BMI) and HbA1c levels were measured. The presence or absence of hypertension was recorded. Results. Men constituted 41.5% of the group, the mean age at diagnosis of T2DM was 50.4 years, and 50.2% were hypertensive. The BMI was 25.0 ± 4.1 kg/m2, and HbA1c was 7.75 ± 1.63% (61.2 ± 17.8 mmol/mol) (mean ± SD, for BMI and HbA1c)). Severe visual impairment/blindness was reported in 10.6%, 15.2% had cataract, 16.0% had retinopathy, and 11.1% had maculopathy. The prevalence of retinopathy increased with time from diagnosis of T2DM (chi-square for trend, p<0.001) and with increasing HbA1c level (chi-square for trend, p=0.03). Conclusion. These results compare well with the most recent results in well-equipped, wealthier regions of the world and show the importance of stable healthcare infrastructure for chronic-disease management.